Power emergency assistant decision methods based on CBR - Yongsheng MEN; Shanbao LIU (Dianxin kexue)
Application of case-based reasoning（CBR）to generate grid infrastructure accidents emergency disposal scheme,can provide auxiliary decision scientific method for emergency people.Through investigation and analysis of the electric accident case,conclude basic situation,disposal process,disposal effect in three aspects of the characteristic attributes presentation framework of power accidents.Search similar case in two methods by means of inductive retrieval and similarity calculation.The determination of membership function of fuzzy attributes by using expert scoring was put forward.Fuzzy attribute similarity by membership functions was calculated and the power accidents case-based reasoning emergency disposal of the auxiliary decision-making process were given.